2018
DOI: 10.1159/000490946
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropin Releasing Hormone Agonist Final Oocyte Maturation and Human Chorionic Gonadotropin as Exclusive Luteal Support in Normal Responders

Abstract: Background/Aims: Gonadotropin releasing hormone (GnRH) agonist triggering results in an endogenous gonadotropin flare. Although it effectively stimulates ovulation, GnRH agonist triggers results in an early luteolysis and requires modification of the luteal support. The current study aims to evaluate GnRH agonist triggering with exclusive human chorionic gonadotropin (hCG) luteal support. Methods: In this prospective observational study, 56 normogonadotropic-assisted reproductive technology patients, stimulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…However, insufficient evidence is available regarding the impact of a GnRHa or a dual trigger on normal responders. A recent observational study reported cycle outcomes following a Gn-RHa trigger with exclusive hCG support in a progesterone-free luteal phase, and the results were comparable to those of cycles triggered by hCG [8]. This study was rare in that it supported a GnRHa trigger as a valid alternative in normal responders.…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…However, insufficient evidence is available regarding the impact of a GnRHa or a dual trigger on normal responders. A recent observational study reported cycle outcomes following a Gn-RHa trigger with exclusive hCG support in a progesterone-free luteal phase, and the results were comparable to those of cycles triggered by hCG [8]. This study was rare in that it supported a GnRHa trigger as a valid alternative in normal responders.…”
Section: Introductionmentioning
confidence: 71%
“…They also reported nonsignificant trends towards higher implantation, clinical pregnancy, and live delivery rates in the dual-trigger group compared to the hCG-trigger group [24]. In another recent study, Beck-Fruchter et al [8] compared the results following a Gn-RHa trigger and an hCG trigger in normal responders. The authors reported similar outcomes regarding the number of oocytes, oocyte maturation rate, implantation rate, and live birth rate [8].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation